A Simple Comparative Analysis on Self-Medication Knowledge and Effort of Health and Non-Health Students in Universitas Islam Negeri Sumatera Utara - Wahyudi Wahyudi; Vera Estefania Kaban (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Self medication has advantages such as increases access to medication and also can contribute to reducing prescribed drug costs. This study aims to describe the comparison of knowledge and efforts of self-medication health students (Faculty of Public Health/FPH) and non-health students (Faculty of Science and Technology/FST) in State Islamic University Of North Sumatera. This research is a quantitative descriptive study using survey methods. Data collection was carried out using a questionnaire through the Google form which was then analyzed to be able to describe the results of the research. The research was conducted on 100 students (FPH n=50 and FST n=50) were students in semesters 1-6. Self-medication knowledge on very good category are 80% for FPH and 16% for FST. The good category is 12% for FPH and 24%, the moderate category is for 4% FPH and 44% FST, the bad category is for 4% FPH and 12% FST, and the very bad category for FPH is absent and 4% for FST. Self-medication knowledge on very good category are 72% for FPH and 28% for FST. The good category is 18% for FPH and 26%, the moderate category is for 8% FPH and 36% FST, the bad category is for 2% FPH and 4% FST, and the very bad category for FPH is absent and 6% for FST. Health and non-health students both like the tablet drug form with a percentage of 56% and 64% respectively. Conclusion- The conclusion of this study is that FPH students have a much better level of knowledge and self-medication efforts than FST. This could be because FPH students have a background in health education. Keywords: Knowledge, Medicine, Self-Medication, Student.